Content Validity Ratio (CVR), Content Validity Index (CVI) and Confirmatory Factor Analysis (CFA) in Mathematics Learning Independence Instruments - Irfan Wahyu Prananto; Yeni Rakhmawati; Tubagus Pamungkas (Universitas Islam Sultan Agung, 2022)
Learning independence is one of the essential things in the learning process. The demand for independent learning is enormous in the learning process at school, especially in mathematics. If responded to appropriately, these demands can help future students' psychological development. The purpose of this study was to measure the content validity of the mathematics learning independence scale to obtain instruments that are right on target. This study uses a type of quantitative research. A sample of one hundred and twenty-six students was obtained from public elementary schools in Tlogowungu District, Pati Regency. Data analysis uses the equation CVR (Content Validity Ratio), CVI (Content Validity Index), and CFA (Confirmatory Factor Analysis). The results showed that 26 of 30 items were declared valid and had a CVI value of 0.911. In contrast, for CFA, the relationship for the three indicators of learning independence was relatively high,> 0.5. This indicates that the three indicators are related; they can both measure the learning independence variable. So, the three indicators can measure learning independence variables well.